ANALISIS FRAMING PEMBERITAAN PIDATO MENTERI NADIEM MAKARIM PADA PERINGATAN HARI GURU NASIONAL - Nove Kurniati Sari (LPPM Universitas Abdurrab, 2020)
Nadiem Makarim is part of the Jokowi cabinet which received pros and cons responses from the public. His background as a businessman has been criticized by various parties who doubt his capacity in government. Criticism of Nadiem was also given in the text of his speech on Teacher's Day which was considered different from other formal public speeches. The method in this study uses Robert N. Entman's framing analysis model to explore the perspective of online media on Nadiem Makarim's speech text. The author argues, using framing analysis, the construction of events presented by the media can be understood from various points of view and lead public interpretations as objectively as possible. The purpose of this study is to find differences between the media in processing and presenting facts about an event. The results of this study indicate that each media has its own characteristics in preaching the Teacher's Day speech by Nadiem Makarim. Liputan6 presents the news from the standpoint of Nadiem's ​​concern for national education. Whereas Pontas.id, Republika.co.id, and CNNIndonesia.com use the perspective of educational leaders in criticizing aspects of the application and prospects of the essence of the speech text.